2011
DOI: 10.1016/j.physleta.2011.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbits for classical particles having complex energy

Abstract: This paper revisits earlier work on complex classical mechanics in which it was argued that when the energy of a classical particle in an analytic potential is real, the particle trajectories are closed and periodic, but that when the energy is complex, the classical trajectories are open. Here it is shown that there is a discrete set of eigencurves in the complex-energy plane for which the particle trajectories are closed and periodic.Comment: 12 pages, 9 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…and make contact with the model studied in Anderson et al [48]. As explained in Cavaglia et al [18], integrating (4.6) twice with respect to ζ , we obtain with integration constants κ 1 , κ 2 ∈ C. Identifying u → x and ζ → t for the travelling wave equation, together with the constraints…”
mentioning
confidence: 63%
“…and make contact with the model studied in Anderson et al [48]. As explained in Cavaglia et al [18], integrating (4.6) twice with respect to ζ , we obtain with integration constants κ 1 , κ 2 ∈ C. Identifying u → x and ζ → t for the travelling wave equation, together with the constraints…”
mentioning
confidence: 63%
“…The quantum‐classical transitions in complex space for model systems, including the free Gaussian wave packet, the harmonic oscillator, and the Morse potential, have been analyzed using complex transition trajectories. In addition, complex classical trajectories have attracted considerable interest due to similarities between complex classical mechanics and quantum mechanics in the last decade . It has been shown that many quantum features can be reproduced in the context of complex classical mechanics.…”
Section: Discussionmentioning
confidence: 92%
“…While complex classical mechanics is a relatively new field there have already been many papers published on the properties of complex phase space . Most of these studies have focused on Hamiltonians of the form H(x,p)=p2+V(x).…”
Section: Introductionmentioning
confidence: 99%